2011
DOI: 10.1021/cm200546r
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Crystalline Phases of Poly(2,6-Dimethyl-1,4-phenylene)oxide

Abstract: Crystalline modifications, exhibiting largely different X-ray diffraction\ud patterns, have been obtained for poly(2,6-dimethyl-1,4-phenylene)oxide (PPO), by\ud gel desiccation procedures as well as by solvent-induced crystallization of amorphous\ud films. The choice of the solvent allows controlling the nature of the crystalline phase.\ud Both amorphous and semicrystalline samples of this commercial thermoplastic\ud polymer exhibit a high uptake of large guest molecules (like, e.g., benzene or carbon\ud tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
111
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 99 publications
3
111
1
Order By: Relevance
“…In addition to these microporous polymer materials, the formation of microporouscrystalline forms (often referred as nanoporous crystalline forms in the literature), presenting a density lower than the corresponding amorphous phase, have been also discovered for two industrially relevant polymers: syndiotactic polystyrene (s-PS) [10][11][12][13][14][15][16][17] and poly(2,6-dimethyl-1,4-phenylene)oxide (PPO) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these microporous polymer materials, the formation of microporouscrystalline forms (often referred as nanoporous crystalline forms in the literature), presenting a density lower than the corresponding amorphous phase, have been also discovered for two industrially relevant polymers: syndiotactic polystyrene (s-PS) [10][11][12][13][14][15][16][17] and poly(2,6-dimethyl-1,4-phenylene)oxide (PPO) [18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The diffraction data reported in Figure indicate that, depending on the solvent, different crystalline phases can be obtained after solvent removal from the gels. It is worth adding that additional crystalline phases have been obtained after treatment with supercritical carbon dioxide of PPO gels prepared in other solvents such as α‐pinene, 1,2‐dichloroethane, tetralin,
…”
Section: Resultsmentioning
confidence: 99%
“…Very recently it has been shown that poly(2,6‐dimethyl‐1,4‐phenylene)oxide (PPO) can also form various nanoporous crystalline phases presenting much higher solubility of many guests (e.g., benzene, CCl 4 , CO 2 , methane, propane, and propene) than fully amorphous PPO. Moreover with respect to s‐PS, PPO presents the advantage to also possess a high melting temperature of the nanoporous crystalline phases at c.a.…”
Section: Introductionmentioning
confidence: 99%
“…While the preparation and the characterization of amorphous nanoporous polymeric materials such as hyper‐cross‐linked polymer networks (HCPs) or linear rigid polymers with intrinsic porosity (PIMs) are well‐documented in the literature the existence of nanoporous polymeric crystalline phases has been described so far only for syndiotactic polystyrene (s‐PS) and poly(2,6‐dimethyl‐1,4‐phenylene ether) (PPO) . These commercially available thermoplastic polymers are able to form co‐crystalline phases with several low‐molecular‐mass guest molecules which, in turn, by suitable guest extraction procedures, can give nanoporous crystalline forms.…”
Section: Introductionmentioning
confidence: 99%